Doutorado e Mestrado - Mazzocato, Sandra Bordini; Camatti, Tassiara Baldissera; Träsel, Marcelo Ruschel; Lesnovski, Ana Flávia M.; Silva, Ivana Almeida da; Gomes, Victor Márcio Laus Reis; Pires, Letícia Corrêa (Revista FAMECOS, 2015)
.